Some reflections on South-East Asian export industrialization - Fernando Fajnzylber (CEPAL Review, 1981)
The successful export strategics of some South-East Asian countries have been raised in certain Latin American circles to the level of veritable paradigms and it is held that our region shoidd imitate these processes in order to achieve high rates of growth of production, employment, productivity and even real remuneration. For this reason, it is of particular interest to analyse the policies, institutional machinery, and domestic and international social and political conditions within the framework of which these cases have taken place.